2016
DOI: 10.5935/0100-4042.20160028
|View full text |Cite
|
Sign up to set email alerts
|

UNDERSTANDING THE CHEMICAL PROCESS RELATED TO THE BIOACTIVATION OF SIMVASTATIN THROUGH EXPERIMENTAL ANDIN SILICOMETHODS: A PRACTICAL CLASS

Abstract: high concentration can be an important risk factor for coronary diseases and atherosclerotic lesions. This lipid presents an endogenous biosynthesis that involves several steps; one of them is modulated by the enzyme 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA reductase). HMG-CoA reductase is inhibited by statins, such as simvastatin, in order to reduce seric become active. The structure of simvastatin has a lactone ring that undergoes enzymatic hydrolysis giving the 3,5-dihydroxy-heptanoate metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Por fim, as estratégias de aprendizagem (item 3) precisam ser melhoradas de acordo com as opiniões registradas. É verdade que a FCF-USP ainda adota aulas teóricas e métodos puramente expositivos para muitos dos cursos que compõem as ciências farmacêuticas, ainda que diversos estudos tenham indicado o sucesso de métodos alternativos de ensino, no engajamento estudantil (21)(22)(23)(24)(25). Em concordância às respostas registradas está o fato de que diversas instituições tradicionais, que lideram os rankings de avaliação de desempenho pela crítica especializada, lançam mão de métodos modernos e alternativos de ensino-aprendizagem (também chamado de "Ensinagem"), os quais envolvem, por exemplo, métodos ativos de ensino, onde alunos são os principais objetos do processo de aprendizagem, e os professores assumem o papel de facilitadores deste processo.…”
Section: Processamento Dos Dadosunclassified
“…Por fim, as estratégias de aprendizagem (item 3) precisam ser melhoradas de acordo com as opiniões registradas. É verdade que a FCF-USP ainda adota aulas teóricas e métodos puramente expositivos para muitos dos cursos que compõem as ciências farmacêuticas, ainda que diversos estudos tenham indicado o sucesso de métodos alternativos de ensino, no engajamento estudantil (21)(22)(23)(24)(25). Em concordância às respostas registradas está o fato de que diversas instituições tradicionais, que lideram os rankings de avaliação de desempenho pela crítica especializada, lançam mão de métodos modernos e alternativos de ensino-aprendizagem (também chamado de "Ensinagem"), os quais envolvem, por exemplo, métodos ativos de ensino, onde alunos são os principais objetos do processo de aprendizagem, e os professores assumem o papel de facilitadores deste processo.…”
Section: Processamento Dos Dadosunclassified
“…Nonetheless, this method is not always able to captivate the student the same way as a practical approach . Recently, several efforts to develop new didactic strategies to teach medicinal chemistry to both undergraduate and graduate pharmacy and chemistry students have shown that practical approaches are able to more effectively reach the students and consequently lead them to a deeper understanding about the theoretical aspects. Hence, allowing a student to explore the drug–target complex three-dimensionally and the locus of interactions may increase the student’s comprehension of all variables related to the formation of the ligand–target complex. , …”
Section: Introductionmentioning
confidence: 99%